Examining the construct validity of the Thai version of the 2 x 2 Achievement goal orientation scale in undergraduate students - Chanut Poondej (Arizona State University, 2016)
In the achievement motivation literature, researches focusing on a concept of the 2 x 2 achievement goal framework are increasingly. However, evidences that support the reliability and validity of this framework are still needed. The purpose of this study was to validate the construct of Thai version of the 2 x 2 Achievement goal orientation scale by using confirmatory factor analysis. This scale was designed to measure the type of students motivational orientations toward learning achievement. The participants of this study involved 518 undergraduate students in Thailand. The descriptive statistics and reliability estimates were analyzed in the current sample. The results support the construct validity of four-factor structure of achievement goal orientation scale. This study contributed empirical evidences and cross-cultural validity of achievement goal orientation in terms of the 2 x 2 achievement goal framework (mastery-approach, mastery-avoidance, performance-approach, and performance-avoidance goal orientations).